Depletion of mitochondrial DNA in leucocytes harbouring the 3243A→G mtDNA mutation. Issue 1 (1st September 2006) - Pyle, Angela; Taylor, Robert W; Durham, Steve E; Deschauer, Marcus; Schaefer, Andrew M; Samuels, David C; Chinnery, Patrick F
Abstract : Background: The 3243A→G MTTL1 mutation is the most common heteroplasmic mitochondrial DNA (mtDNA) mutation associated with disease. Previous studies have shown that the percentage of mutated mtDNA decreases in blood as patients get older, but the mechanisms behind this remain unclear. Objectives and method: To understand the dynamics of the process and the underlying mechanisms, an accurate fluorescent assay was established for 3243A→G heteroplasmy and the amount of mtDNA in blood with real-time polymerase chain reaction was determined. The amount of mutated and wild-type mtDNA was measured at two time points in 11 subjects. Results: The percentage of mutated mtDNA decreases exponentially during life, and peripheral blood leucocytes in patients harbouring 3243A→G are profoundly depleted of mtDNA. Conclusions: A similar decrease in mtDNA has been seen in other mitochondrial disorders, and in 3243A→G cell lines in culture, indicating that depletion of mtDNA may be a common secondary phenomenon in several mitochondrial diseases. Depletion of mtDNA is not always due to mutation of a nuclear gene involved in mtDNA maintenance.